Waste chestnut shell as a source of reinforcing fillers for polypropylene composites - Kaymakci, Alperen; Ayrilmis, Nadir (SAGE Publications, 2012)
In this study, we evaluated dimensional stability and some mechanical properties of polypropylene composites filled with chestnut shell flour (CSF). To meet this objective, CSF was compounded with polypropylene with and without coupling agent in a twin screw corotating extruder and then were manufactured by injection molding process. The thickness swelling and water absorption of the samples increased with increasing CSF content. The flexural and tensile modulus improved with increasing CSF content, while the flexural and tensile strengths of the samples decreased. The use of maleic anhydride polypropylene had a positive effect on the dimensional stability and mechanical properties of the polypropylene composites filled with CSF. This work showed that the composites treated with maleated polypropylene could be efficiently used as decking products, due to high-dimensional stability and satisfactory mechanical properties of the composites.
Keywords: 13. Climate action